Elderly Monitoring – An EPS@ISEP 2020 Project - Priebe, Julian (2021)
In the spring of 2020, six undergraduate students from diverse countries and engineering fields decided to design together a solution to monitor the elderly. This project was performed as part of the European Project Semester (EPS) programme at Instituto Superior de Engenharia do Porto (ISEP). The EM-BRACE solution encompasses two interconnected devices (a home station and a bracelet) and mobile/Web twin applications. The bracelet measures and transmits vital user data (pulse, temperature and impacts) to the home station, whereas the latter measures home environment parameters (temperature, humidity and pressure) and sends local and bracelet data to an Internet of Things (IoT) platform. This way, these data become accessible via the mobile/Web application. Thereby, EM-BRACE monitors the health and environment of the elderly and timely notifies caregivers about problems, contributing to the well-being of the elderly and their families.